Jurisdiction Overview Criminal Action of Obstacling the Judicial Process (Obstruction of Justice) Performed by Doctor - Andre, Gusti Muhammad; Setiyono, Joko (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Obstruction of justice is an act of someone who obstructs the legal process and disrupts the proper function in a judicial process. The act of obstruction of justice is an act against the law that bypasses and opposes law enforcement. Normatively, the act of obstructing the judicial process has been regulated in many regulations, both in the Criminal Code and in special criminal law. The problems discussed by the author are how the form of acts of obstructing the judicial process (obstruction of justice) carried out by doctors in positive law in Indonesia and how criminal liability by doctors who commit criminal acts hindering the judicial process (obstruction of justice). The method that the author uses in this research is a normative legal approach method using secondary data sources which include primary legal materials, secondary legal materials and tertiary legal materials. The results of the research and discussion show that: the form of the act of obstructing the judicial process (obstruction of justice) carried out by the doctor that the act is all forms of intervention to the entire legal and justice process from the beginning until the process is completed both at the stage of the investigation, prosecution and the judge. In terms of the criminal liability of the medical profession who intentionally prevents, hinders, hinders, or thwarts directly or indirectly the investigation, prosecution, and examination in court against suspects and defendants or witnesses in corruption cases (Obstruction of Justice), Corruption Crimes have regulated in criminal law in Indonesia in Article 21 of Law 20 of 2001 on the replacement of Law Number 31 of 1999 concerning the Eradication of Corruption.